Nonlinear stochastic functional integral equations in the plane. (1995) - Turo, Jan
Abstract : Local or global existence and uniqueness theorems for nonlinear stochastic functional integral equations are proved. The proofs are based on the successive approximations methods. The formulation includes retarded arguments and hereditary Volterra terms.